2019
DOI: 10.15171/apb.2019.066
|View full text |Cite
|
Sign up to set email alerts
|

Niosomal Benzoyl Peroxide and Clindamycin Lotion Versus NiosomalClindamycin Lotion in Treatment of Acne Vulgaris: A RandomizedClinical Trial

Abstract: Purpose: Combination of benzoyl peroxide (BPO) with topical antibiotics can lead to higher efficacy and less bacterial resistance, but it in turn increases adverse effects such as skin irritability and dryness. In this study, the efficacy of combination therapy of niosomal BPO 1% and clindamycin (CL) 1% is compared with niosomal CL in acne vulgaris. Methods: This is a double-blind clinical trial study on 100 patients with acne vulgaris in Afzalipour hospital in Kerman. Patients were randomly divided into 2 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 15 publications
(17 reference statements)
3
16
0
Order By: Relevance
“…Also, combination of benzoyl peroxide 1% and clindamycin 1% showed higher efficacy with no increase in adverse effects in comparison with clindamycin 11 (3) Azelaic acid 20% cream was shown to better reduce seborrhea in our study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Also, combination of benzoyl peroxide 1% and clindamycin 1% showed higher efficacy with no increase in adverse effects in comparison with clindamycin 11 (3) Azelaic acid 20% cream was shown to better reduce seborrhea in our study.…”
Section: Discussionsupporting
confidence: 54%
“…showed higher efficacy with no increase in adverse effects in comparison with clindamycin. 11 (3) Azelaic acid 20% cream was shown to better reduce seborrhea in our study. In today's recommendations, it is used to treat postinflammatory hyperpigmentation from acne.…”
Section: Absolute Value Percentagesupporting
confidence: 48%
“…The studies investigated the use of topical nadifloxacin and benzoyl peroxide, clindamycin and benzoyl peroxide, combined retinaldehyde and glycolic acid cream, adapalene and benzoyl peroxide, erythromycin and zinc acetate and several dermocosmetic products. The pretreatment and post‐treatment CADI scores were reported in 10 studies 30,31,42,43,45–47,49–51 . One study 48 reported the percentage improvement and two studies gave a descriptive account of QoL improvement 41,44 .…”
Section: Resultsmentioning
confidence: 99%
“…The CADI has been used in 13 studies 30,31,[41][42][43][44][45][46][47][48][49][50][51] describing pharmacological topical interventions (Table 2). The studies investigated the use of topical nadifloxacin and benzoyl peroxide, clindamycin and benzoyl peroxide, combined retinaldehyde and glycolic acid cream, adapalene and benzoyl peroxide, erythromycin and zinc acetate and several dermocosmetic products.…”
Section: Topical Drug Interventionsmentioning
confidence: 99%
See 1 more Smart Citation